UTILIZING LEARNING PLATFORM FOR PAPERLESS CLASSROOM - Wenty Dwi Yuniarti (Vision: Journal for Language and Foreign Language Learning, 2014)
Technology, in the present time, has been integrated in a variety of human activities, not least in learning. Learning platform provides the integration of technology-based learning environment. Learning platform places technology as “substitute” for a variety of learning activities that previously had to be done manually and must be presented physically to any other form that the virtual tools while providing a social area in order to maintain the importance of the relationship between teacher and student.Through virtual tools, learning platforms provide a learning environment that models the interactions within the class as a whole starting from the preparation of lesson plans, presentation materials, use of media, assignments, group work, assessment, management of the rating value to students. Support for learning administrative aspects are available through the authorization feature and access scope management that aims to clarify the roles, forms of participation and the interaction process of each of group involved in the learning, both students, teachers and system administrators.The variety of learning platform is available either in the form of open source or limited use, either in the form of package systems such as Learning Management System via Moodle and cloud-based tools such as Google’s Classroom, etc. Haiku learning. The following section will describe the use of virtual tools in a learning platform for implementing learning environment as a whole. One thing that can not be avoided and instead be more value in the use of learning platforms are the creation of a new paradigm of learning without paper. Except giving a new form for efﬁcient and optimal learning, in the perspective of the present paperless classroom certainly economical and environmentally friendly.